The favourite whipping boy - Gill, S.S. (2001)
This paper suggests that even though the bureaucracy had become the favourite whipping boy, (especially of the media) the fact was that most of the ills ascribed to it could actually be traced to the depravity of the political class. Moreover, while the media highlighted all the negative aspects of bureaucracy, positive interventions and success stories - like the successful conduct of the Kumbh Mela were never brought to public focus. - Reproduced.
Keywords: Bureaucracy